1996
DOI: 10.1007/bf01377206
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal involvement in pediatric neurofibromatosis: a case report and review of the literature

Abstract: A case of neurofibroma of the larynx occurring in generalized neurofibromatosis (von Recklinghausen's disease) is presented, and the previously reported pediatric cases are reviewed. Laryngeal involvement in neurofibromatosis is rare and the predominant signs and symptoms include dyspnea, stridor, loss or change of voice and dysphagia. Problems posed related to diagnosis, management and course of this infrequent laryngeal localization are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
0
11
0
3
Order By: Relevance
“…Speech problems were reported in 60% of children with NF1 and in 5% of unaffected siblings in response to specific questions on the CBCL. Concerning the nature of speech disorders in NF1 patients, several authors mentioned the occurrence of articulation disorders (Ransom et al 2006, Sobol et al 1997) and voice abnormalities (Yucel et al 2002, Masip et al 1996) associated with head and neck neurofibromas. In addition, White et al (1986) stated that the speech of a patient with NF1 is characterized by hypernasality, a deliberate paced rhythm, poor strength, and lisping articulations.…”
Section: Introductionmentioning
confidence: 99%
“…Speech problems were reported in 60% of children with NF1 and in 5% of unaffected siblings in response to specific questions on the CBCL. Concerning the nature of speech disorders in NF1 patients, several authors mentioned the occurrence of articulation disorders (Ransom et al 2006, Sobol et al 1997) and voice abnormalities (Yucel et al 2002, Masip et al 1996) associated with head and neck neurofibromas. In addition, White et al (1986) stated that the speech of a patient with NF1 is characterized by hypernasality, a deliberate paced rhythm, poor strength, and lisping articulations.…”
Section: Introductionmentioning
confidence: 99%
“…9 Chang-Lo et al reviewed the worldwide literature in 1975 and identified 19 pediatric cases and in 1996, Masip et al re-reviewed the world literature and identified 21 pediatric cases and until now represented the largest review of literature for pediatric LNF. 2,4 This comprehensive review of the world literature in 2012 demonstrates that there have been 62 cases of pediatric LNF identified in case reports and case series. Table 1 lists all identified case reports and series published since 1940.…”
Section: Discussionmentioning
confidence: 99%
“…1 Pediatric LNFs by comparison are quite rare with conflicting numbers reported in the literature. 24 Prior to 1990, the majority of patients with LNF were treated with open surgical resection. Recently there has been a trend towards the use of minimally invasive endoscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Más que las imágenes neurorradiológicas, los déficits neurológicos progresivos deberían ser los que dictaran la necesidad de la cirugía [8]. La mayoría de los casos publicados durante las últimas dos décadas ha ocurrido en niños [4,[6][7][8][10][11][12][16][17][18], incluyendo la presentación en un recién nacido con apnea causada por el tumor localizado en la unión craneocervical con compresión de la zona cervical superior y la bulbar inferior, que causaba apnea completa y, finalmente, la muerte a la edad de 5 meses [3]. La mayoría de los tumores es asintomática y, en nuestra serie, sólo un paciente (caso 3) tenía crecimiento del tumor intralaríngeamente y causaba obstrucción del paso del aire, además del ensanchamiento del cuello en el lado con el NFP laríngeo, que requería resección y repetición de la intervención quirúrgica cinco años después por recidiva.…”
Section: Discussionunclassified